Ecological features of feather microbiota in breeding common swifts. Issue 6 (2nd November 2018) - Musitelli, Federica; Ambrosini, Roberto; Caffi, Mario; Caprioli, Manuela; Rubolini, Diego; Saino, Nicola; Franzetti, Andrea; Gandolfi, Isabella
Abstract : We provide the first-ever investigation of feather microbiota by high throughput DNA sequencing for any bird species by describing bacteria found on the innermost tertial feather of 22 adult common swifts ( Apus apus ). We found feather microbiomes with large abundance of Bacillales, Actinomycetales, Burkholderiales, Sphingobacteriales, Sphingomonadales, Rhizobiales, Pseudomonadales, Clostridiales, Rubrobacterales and Lactobacillales. Bacterial communities did not change with any feature of individual swifts. Network and cluster analysis of feather microbiomes disclosed three clusters, characterized by bacteria typical of seawater, plants and soil and unrelated to conditions at the breeding grounds. We hypothesize that feather microbiomes reflect, at least partly, airborne bacterial communities of the environments where individuals spent non-breeding periods, or of those that they crossed during migration, rather than breeding environment. If confirmed, this evidence may disclose the possibility to use feather bacteria as proxies for tracing non-breeding origin and routes of migratory birds.